Copyright law in the digital environment: DRM systems, anti-circumvention, legislation and user rights - Latter, Gareth Paul (Rhodes University, Faculty of Law, Law, 2012)
This thesis deals with the way in which copyright law is changing in the digital environment and the mechanisms which are facilitating this change. It deals with these issues by analysing the mechanisms of this change, specifically Digital Rights Management (DRM)Systems and anti-circumvention legislation, and the impact which this change is having on the rights of copyright users. The purpose of copyright is to provide an incentive to authors to continue creating while simultaneously providing a public good in allowing the public to use those creations in certain ways. Copyright achieves this purpose by granting both the author and user certain rights. The author is given a limited monopoly over their work in exchange for allowing this work to enter the public sphere and ensuring that users of that work can utilise that work in certain limited ways. The success of copyright thus rests on maintaining the balance between the rights of these parties. The rise of digital technology has created a situation in which copyright content can be easily copied by any party with a Personal Computer and disseminated around the globe instantly via the Internet. In response to these dangers, copyright owners are making use of DRM systems to protect content. DRM systems include various measures of control within its scope. Theses systems allow for copyright owners to control both access and use of content by copyright users. DRM Systems are not foolproof measures of protection however. Technologically sophisticated users are able to circumvent these protection measures. Thus, in order to protect DRM Systems from circumvention, anti-circumvention legislation has been proposed through international treaties and adopted in many countries. The combined effect of these protection measures are open to abuse by copyright owners and serve to curtail the limited rights of copyright users. The end result of this is that the balance which copyright law was created to maintain is disrupted and copyright law no longer fulfils its purpose. This thesis undertakes an analysis of these issues with reference to how these issues affect copyright users in developing countries. This is done with particular reference to possible approaches to this issue in South Africa as South Africa is a signatory to these anti-circumvention treaties.
Keywords: Digital rights management; Copyright and electronic data processing; Internet -- Law and legislation; Public domain (Copyright law); Fair use (Copyright); Intellectual property; Copyright